2019
DOI: 10.3390/molecules24030645
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Docking of DNA Repair Proteins Associated with Cancer Survival Following PCNA Metagene Adjustment: A Potential Novel Class of Repair Inhibitors

Abstract: Natural and synthetic small molecules from the NCI Developmental Therapeutics Program (DTP) were employed in molecular dynamics-based docking with DNA repair proteins whose RNA-Seq based expression was associated with overall cancer survival (OS) after adjustment for the PCNA metagene. The compounds employed were required to elicit a sensitive response (vs. resistance) in more than half of the cell lines tested for each cancer. Methodological approaches included peptide sequence alignments and homology modelin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…In line with this, we and others have reported that inhibition of the DNA-dependent protein kinase catalytic subunit radio-sensitizes GBM and GSCs by inducing apoptotic cell death ( Timme et al, 2018 ; Fang et al, 2021 ). Many studies have also shown that natural compounds can inhibit DNA repair machinery when coupled with radiation, thereby acting as radio-sensitizing agents ( Peterson, 2019 ). In our study, we observed that PBI-05204 could attenuate DNA repair after RT as indicated by increased expression and permanence of γH2Ax over time and reduction of Rad51 and DNA-PKCs.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, we and others have reported that inhibition of the DNA-dependent protein kinase catalytic subunit radio-sensitizes GBM and GSCs by inducing apoptotic cell death ( Timme et al, 2018 ; Fang et al, 2021 ). Many studies have also shown that natural compounds can inhibit DNA repair machinery when coupled with radiation, thereby acting as radio-sensitizing agents ( Peterson, 2019 ). In our study, we observed that PBI-05204 could attenuate DNA repair after RT as indicated by increased expression and permanence of γH2Ax over time and reduction of Rad51 and DNA-PKCs.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison between the ligand amounts bound with (a) DNApolβ and (b) HSA show that the ligand-enzyme complex includes two molecules of ligand per one molecule of enzyme, while the ligand-HSA (control) pair contains just one ligand per HSA molecule (Figures 4,7,8). This is in favor to a mere fact of existence of two separate Mg 2+ -coordinating catalytic sites in β-and β-like DNA polymerases [8,10,[21][22][23]. Now, we evaluate the activation energy value for a ligand-enzyme complex dissociation following the data listed in Figure 4; Figure 8.…”
Section: Discussionmentioning
confidence: 99%
“…The physical properties of flavonoids and prediction of their toxicology and Absorption, Distribution, Metabolism, Excretion (ADME) was performed using methods described previously (Peterson, 2019).…”
Section: Toxicology and Adme Predictionsmentioning
confidence: 99%